2013
DOI: 10.1080/10916466.2010.551244
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Effects of the Reservoir Variables and Operational Parameters on Steam-Propane Injection Performance

Abstract: The application of steam injection in different forms of processes is widely used as thermal heavy oil recovery. Several studies have been carried out to evaluate the effect of injecting steam with gaseous additives such as hexane, nitrogen, carbon dioxide, methane, and propane. One of the most useful additives to steam is propane. The use of propane has been found to accelerate oil production due to dry distillation process in which light hydrocarbon fractions evaporated and carried by propane. In contact wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The evaluation of oil recovery after and before steam-propane injection is utilized as the basis of the analysis. The graph is analyzed to see how effective the model is in terms of oil recovery from a given period [13,14]. The procedure used to conduct this study is shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…The evaluation of oil recovery after and before steam-propane injection is utilized as the basis of the analysis. The graph is analyzed to see how effective the model is in terms of oil recovery from a given period [13,14]. The procedure used to conduct this study is shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…Mohebati (2012) separately optimized hydrocarbon additives in SAGD for three different oil-sand deposits and determined the appropriate amount of hydrocarbon injection [13]. Dehghan (2013) optimized the manner of development on the base of an actual heavy oil reservoir for steampropane injection [14]. Dong (2015) indicated that SAGP was also applicable to thick heavy oil reservoir [15].…”
Section: Introductionmentioning
confidence: 99%